Strategi Marketing Public Relation Gramedia Matraman Dalam Mempertahankan Eksistensi - Diki Abdullah; RR Roosita Cindrakasih; Rizky Hidayat (Tamilis Synex: Multidimensional Collaboration, 2025)
Currently the business world is facing major changes in industry, changes that make all kinds of businesses face difficult challenges. The change in question is the presence of the digitalization phenomenon and changes in consumer interest in consumption or shopping. Various types of businesses are having difficulty dealing with this phenomenon, especially retail businesses that focus on bookstores. Many bookstores, both independent and part of large chains, have to compete with online-based digital bookstores. Many consumers appreciate Gramedia, because of its complete book collection. This is what makes Gramedia a leading retail company and book publisher in Indonesia. Currently, no business can survive without adapting to technological developments. Therefore, this research aims to understand how the Marketing Public Relations strategy of the Gramedia Matraman bookstore is able to adapt to changes in consumer behavior amidst the dynamic digitalization phenomenon. They have not only succeeded in maintaining relationships with their loyal consumers both through physical stores and digital platforms. This research uses a qualitative approach, which describes each information obtained with a clear explanation. The type of approach used is descriptive, where descriptive research aims to explain solutions to existing problems based on the data collected. The data collection techniques used by researchers in research are interviews, observation, literature study and documentation. The research results show how Gramedia Matraman's Marketing Public Relations (MPR) strategy is implemented in maintaining its existence